Clinicopathological features and survival of early stage breast cancer in northwest China: A population‐based retrospective study of 1287 patients. Issue 1 (4th October 2017) - Li, Shuting; Wang, Xiangtang; Yang, Jiao; Lv, Meng; Zhang, Xiao; Li, Chunli; Zhang, Lingxiao; Shen, Yanwei; Zhang, Xiaoman; Chen, Zheling; Wang, Fan; Wang, Xin; et al.
Abstract : Background: Breast cancer (BC) displays different clinicopathological features and outcomes based on patient age, molecular subtype, and treatment. However, such features in BC patients in northwest China are unclear. This study investigated the clinicopathological features and overall survival (OS) of early stage BC patients using a population‐based study. Methods: Patients who were newly diagnosed with BC at the First Affiliated Hospital of Xi'an Jiaotong University between January 2001 and June 2012 were included. Clinicopathological features and OS were assessed. Results: The median age of 1287 patients was 50 years, with an average tumor size of 2.65 cm. Additionally, 42.7% were luminal A, 25.6% luminal B, 9.3% Her2 overexpression, and 17.7% triple negative. The cut‐off age was 35 years, and young patients (< 35) tended to have larger tumors, ≥ 4 positive lymph nodes, grade 2 or 3 histology, non‐luminal types, high Ki67, and poor outcomes. Patients with luminal A tumors showed moderate features: 50.6% had tumors < 2 cm, 56.7% had negative lymph nodes. Patients with Her2 overexpression tumors showed aggressive features and the poorest survival (5‐year OS 67.6%). Patients with triple negative tumors were the youngest (average 48.4 years), but had the largest proportion of grade 3 histology and poor outcomes. Conclusion: Our results are consistent with those in other provinces in China, but showed an earlier age at diagnosis and more aggressive pathological features compared to developed countries. Additionally, each molecular subtype showed specific features and different survival outcomes.